CONTRIBUTIONS REGARDING THE DEVELOPMENT OF THE SPEED OF MOVEMENT THROUGH SPECIFIC MEANS OF THE FOOTBALL GAME IN THE PHYSICAL EDUCATION LESSON IN THE SIXTH GRADE OF BAC?U - ROMANIA (Fiep Bulletin - online, 2020)
This research aims to create a model of the development of the speed of movement through specific means of the football game in the physical education lesson in the sixth grade.Being a very dynamic game practiced under intense global, physical and physiological demands, in which contact with the opponent is not excluded, football is a precious means of physical education, both in terms of instructional effects and, if well valorized educational, and as an excellent means of forming moral-volitional qualities and invaluable character traits.The subjects of this research were sixth graders of the ”Miron Costin” General School in Bac?u. The experiment was conducted between March and June, 2019, with class VI, consists of 24 students, of which: 10 boys and 14 girls.The specific football action means were conceived and conducted within the allocated time of the physical education lesson of 50 minutes. The experiment consisted of an initial testing (March 6, 2019), comprising control challenges, obtaining initial data for the experiment, one intermediary tests (April 20, 2019), and a final testing (May 29, 2019), at the end of the experiment, through which the final data of the experiment was recorded, using the same challenges.Between the initial and the final testing, the established training means and programs were applied. During the experiment, the subjects' progress was verified by two control tests: 5x10 meter shuttle - girls / boys and 50 meters speed run - girls / boys.At the end of the experiment and after analyzing the recorded results, we are able to state that the correct use of certain means of action specific to the game of football in class VI ensures the development of the speed of movement.